Acarapidosis of bees, prevention and treatment measures - Rakhimov Mukhamad Yunusovich (Genius Journals, 2022)
The article provides information on the prevention and treatment of varroatosis, which occurs in bees and causes great economic damage. This disease is an invasive disease that is acute and chronic. In the prevention of disease, it is advisable to ensure the zoo hygienic conditions of the environment and the exchange of effective drugs against diseases.
Keywords: Varroatosis; mite; pyretroid; waxed cage